Die symmetrischen Mannigfaltigkeiten von Zentralkopunktoren - Bliznikas, V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас, Симметрические пространства центральных копункторовV. Bliznikas, Simetrinės centrinių kopunktorių erdvės